Fibroblast drug scavenging increases intratumoural gemcitabine accumulation in murine pancreas cancer. Issue 3 (10th January 2017) - Hessmann, E; Patzak, M S; Klein, L; Chen, N; Kari, V; Ramu, I; Bapiro, T E; Frese, K K; Gopinathan, A; Richards, F M; Jodrell, D I; Verbeke, C; et al.
Abstract : Objective: Desmoplasia and hypovascularity are thought to impede drug delivery in pancreatic ductal adenocarcinoma (PDAC). However, stromal depletion approaches have failed to show clinical responses in patients. Here, we aimed to revisit the role of the tumour microenvironment as a physical barrier for gemcitabine delivery. Design: Gemcitabine metabolites were analysed in LSL-Kras G12D/+ ; LSL-Trp53 R172H/+ ; Pdx-1-Cre (KPC) murine tumours and matched liver metastases, primary tumour cell lines, cancer-associated fibroblasts (CAFs) and pancreatic stellate cells (PSCs) by liquid chromatography-mass spectrometry/mass spectrometry. Functional and preclinical experiments, as well as expression analysis of stromal markers and gemcitabine metabolism pathways were performed in murine and human specimen to investigate the preclinical implications and the mechanism of gemcitabine accumulation. Results: Gemcitabine accumulation was significantly enhanced in fibroblast-rich tumours compared with liver metastases and normal liver. In vitro, significantly increased concentrations of activated 2′, 2′-difluorodeoxycytidine-5′-triphosphate (dFdCTP) and greatly reduced amounts of the inactive gemcitabine metabolite 2′, 2′-difluorodeoxyuridine were detected in PSCs and CAFs. Mechanistically, key metabolic enzymes involved in gemcitabine inactivation such as hydrolytic cytosolic 5′-nucleotidases (Nt5c1A, Nt5c3) were expressed at low levels in CAFs in vitro and in vivo, and recombinant expression of Nt5c1A resulted in decreased intracellular dFdCTP concentrations in vitro. Moreover, gemcitabine treatment in KPC mice reduced the number of liver metastases by >50%. Conclusions: Our findings suggest that fibroblast drug scavenging may contribute to the clinical failure of gemcitabine in desmoplastic PDAC. Metabolic targeting of CAFs may thus be a promising strategy to enhance the antiproliferative effects of gemcitabine.